ANALISIS FAKTOR – FAKTOR RISIKO TERJADINYA MIOPIA BOOMING PADA SISWA DI MTsN 2 JATIASIH KOTA BEKASI - Murni Marlina Simarmata; Siti Asiyah; Zakaria Efendi; Febri Maryani (Jurnal Mata Optik, 2023)
Booming myopia is a condition where the number of people wearing glasses increases because of eye refraction disorders such as nearsightedness. The aim of this study was to analyze risk factors for booming myopia including genetic factors, close viewing activity, lighting and duration for students at MTsN 2 Jatiasih, Bekasi city. This research was conducted descriptively with the method of collecting data in a cross-sectional way using a questionnaire and visual inspection. Data were collected by conducting interviews using questionnaires and visual inspection of the study samples simultaneously during the study. The results of this study include (1) Analysis of risk factors for family history of myopia (Father and Mother/only Father/only Mother) in 52.7% which causes myopia boom in MTsN 2 Jatiasih students, Bekasi city, (2) Activity risk factor analysis close viewing (Reading and using Gadgets, Reading only and using Gadgets only) can be 98.1% which causes booming myopia in MTsN 2 Jatiasih students, Bekasi city, (3) Analysis of risk factors for lighting (Reading and using Gadgets with less lighting, Reading with poor lighting only and using gadgets with only poor lighting) can be 74.5% which causes booming myopia in MTsN 2 Jatiasih students, Bekasi city, (4) Analysis of duration risk factors (reading and using gadgets for more than 2 hours, reading more from 2 hours and using Gadgets for more than 2 hours only) in 90.9% which causes myopia boom in MTsN 2 Jatiasih students, Bekasi city.